2016
DOI: 10.1177/0898264316662359
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Exercise Initiative for Seniors to Improve Balance and Physical Function

Abstract: Objectives: To investigate the feasibility, effectiveness and short term effects of an exercise intervention using a novel exercise park in improving senior's balance, physical function and quality of life. Methods: Randomised controlled trial with pre and post intervention design (Baseline and 18-week intervention). Outcomes measures included measures of balance, strength and function as well as quality of life and fear of falling. Multivariate analysis of covariance was used to assess differences between gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 41 publications
0
43
0
1
Order By: Relevance
“…The full description of the approach and outcomes (methods, design, randomisation process, exercises and assessments) associated with evaluation of the senior exercise park are described elsewhere (Ethics Approval HRE13‐215). This study was conducted between 2013 and 2015.…”
Section: Participants and Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…The full description of the approach and outcomes (methods, design, randomisation process, exercises and assessments) associated with evaluation of the senior exercise park are described elsewhere (Ethics Approval HRE13‐215). This study was conducted between 2013 and 2015.…”
Section: Participants and Methodologymentioning
confidence: 99%
“…significant improvement in lower limb muscle strength, function and balance following 18 weeks of the exercise park program for older people. 9 High adherence (attendance) rates (80%) were evident and were related to participants' enjoyment of exercising outdoors with fun and enjoyable exercises and the associated social interaction. 10 This study is a reflective narrative describing this innovative exercise approach, and reports challenges associated with establishment of the exercise park, conducting the randomised trial, strategies adopted to address these challenges and recommendations for future implementation of this approach in the community.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Worldwide, new urban design initiatives are emerging to transform public spaces, increase physical activity, participation, and social interaction, and reduce the growing burden of chronic diseases, in older adults. Notable recent developments include exercise parks fit for older people's purpose [7,8], smart home technology [9], dementia villages [10], and scoping of 'walkable' neighbourhood design features [11]. Sales et al [8] reported that short-term use of a novel exercise park improved physical function in older adults, and was associated with high rates of adherence and participation.…”
Section: Introductionmentioning
confidence: 99%
“…Notable recent developments include exercise parks fit for older people's purpose [7,8], smart home technology [9], dementia villages [10], and scoping of 'walkable' neighbourhood design features [11]. Sales et al [8] reported that short-term use of a novel exercise park improved physical function in older adults, and was associated with high rates of adherence and participation. However, safety aspects of purpose-built outdoor exercise areas -for example where there is limited control over climatic and environmental changes -require further consideration [7].…”
Section: Introductionmentioning
confidence: 99%